The Arabidopsis LecRK‐VI.2 associates with the pattern‐recognition receptor FLS2 and primes Nicotiana benthamiana pattern‐triggered immunity. (23rd June 2014) - Huang, Pin‐Yao; Yeh, Yu‐Hung; Liu, An‐Chi; Cheng, Chiu‐Ping; Zimmerli, Laurent
Summary Pattern‐triggered immunity (PTI) is broad spectrum and manipulation of PTI is believed to represent an attractive way to engineer plants with broad‐spectrum disease resistance. PTI is activated upon perception of microbe‐associated molecular patterns (MAMPs) by pattern‐recognition receptors (PRRs). We have recently demonstrated that the L‐type lectin receptor kinase‐VI.2 (LecRK‐VI.2) positively regulates Arabidopsis thaliana PTI. Here we show through in vitro pull‐down, bimolecular fluorescence complementation and co‐immunoprecipitation analyses that LecRK‐VI.2 associates with the PRR FLS2. We also demonstrated that LecRK‐VI.2 from the cruciferous plant Arabidopsis remains functional after interfamily transfer to the Solanaceous plant Nicotiana benthamiana. Wild tobacco plants ectopically expressing LecRK‐VI.2 were indeed more resistant to virulent hemi‐biotrophic and necrotrophic bacteria, but not to the fungal pathogen Botrytis cinerea suggesting that, as with Arabidopsis, the LecRK‐VI.2 protective effect in N. benthamiana is bacteria specific. Ectopic expression of LecRK‐VI.2 in N. benthamiana primed PTI‐mediated reactive oxygen species production, mitogen‐activated protein kinase (MAPK) activity, callose deposition and gene expression upon treatment with the MAMP flagellin. Our findings identified LecRK‐VI.2 as a member of the FLS2 receptor complex and suggest that heterologous expression of components of PRR complexes can be used as tools to engineer plant disease resistance to bacteria.